VOLCANIC HAZARD COMMUNICATION USING MAPS: AN EVALUATION OF THEIR EFFECTIVENESS - Haynes K.; Barclay J.; Pidgeon N. (My University, 2007)
Hazard maps are considered essential tools in the communication of volcanic risk between scientists, the local authorities and the public. This study investigates the efficacy of such maps for the volcanic island of Montserrat in the West Indies using both quantitative and qualitative research techniques. Normal plan view maps, which have been used on the island over the last 10 years of the crisis, are evaluated against specially produced three-dimensional (3D) maps and perspective photographs. Thirty-two demographically representative respondents of mixed backgrounds, sex, education and location were interviewed and asked to complete a range of tasks and identification on the maps and photographs. The overall results show that ordinary people have problems interpreting their environment as a mapped representation. We found respondents’ ability to locate and orientate themselves as well as convey information relating to volcanic hazards was improved when using aerial photographs rather than traditional plan view contour maps. There was a slight improvement in the use of the 3D maps, especially in terms of topographic recognition. However, the most striking increase in effectiveness was found with the perspective photographs, which enabled people to identify features and their orientation much more readily. For Montserrat it appears that well labelled aerial and perspective photographs are the most effective geo-spatial method of communicating volcanic risks.
Keywords: VOLCANIC HAZARD MAP; VOLCANIC RISK MAP; MONTSERRAT; VOLCANIC RISK COMMUNICATION; EVALUATION; GEOSPATIAL